2003
DOI: 10.1590/s0100-41582003000100007
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of pectolytic erwinias associated with blackleg of potato in Rio Grande do Sul

Abstract: Erwinia carotovora subsp. atroseptica (Eca), E. carotovora subsp. carotovora (Ecc) and E. chrysanthemi (Ech) may cause potato (Solanum tuberosum) blackleg. To determine the occurrence of these pathogens in the conditions found in the State of Rio Grande do Sul (RS), potato plants showing blackleg symptoms were harvested from 22 fields in nine counties in Serra do Nordeste, Planalto, Depressão Central, and Grandes Lagoas, from September to December of 1999 (Spring-Summer season). Green pepper (Capsicum annuum) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
0
16
1
1
Order By: Relevance
“…This is contradictory to the results of Pérombelon and Hyman (1986) which indicated a lack of growth of Pcc at 37°C, but confirms results of Oliveira et al (2003) who found Pcc to grow at 37°C. The differences in optimal temperatures for growth can have important consequences in industry as a slight decrease in temperature could result in Pcb becoming dominant in the field, and this subspecies has been reported to be more virulent than other Pectobacterium spp.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…This is contradictory to the results of Pérombelon and Hyman (1986) which indicated a lack of growth of Pcc at 37°C, but confirms results of Oliveira et al (2003) who found Pcc to grow at 37°C. The differences in optimal temperatures for growth can have important consequences in industry as a slight decrease in temperature could result in Pcb becoming dominant in the field, and this subspecies has been reported to be more virulent than other Pectobacterium spp.…”
Section: Discussioncontrasting
confidence: 85%
“…This unique characteristic could be used to distinguish Pba from other pathogenic species causing soft rot and blackleg in potato, as proposed by De Boer and Kelman (2001). However, up to 10% of Pba isolated are atypical and able to grow at temperatures above 37°C (Pérombelon and Hyman 1986;Oliveira et al 2003). Using temperature to characterise species might therefore result in incorrect characterisation in cases where atypical isolates are encountered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…are very harmful and occur in a large number of agricultural crops in Brazil, there are few papers published on the pathogen recently. In a survey on potato plants showing blackleg symptoms in 22 fields of nine counties in Rio Grande do Sul State, 55% of the strains were identified as Eca, 44% as Ecc and only 1% as Ech (Oliveira et al, 2003). Arracacha soft rot continues to be a very important postharvest disease during summertime in Brazil, causing severe losses.…”
mentioning
confidence: 99%
“…The predominance of Ech (89.8%) causing soft rot in arracacha roots in Brazil is a novel finding, since previous papers reporting the disease considered Ecc as the predominant one (Romeiro et al, 1988;Lopes & Quezado-Soares, 1997), although based on the identification of few isolates. Lately, Oliveira et al (2003) described Eca (55%) and Ecc (44%) as the predominant subspecies in potato fields in Southern Brazil, which was unexpected, and more recently, Duarte et al (2004) reported a new, atypical potato blackleg strain called E. carotovora subsp. brasiliensis.…”
mentioning
confidence: 99%